In Vivo Recovery of Factor VIII: A Comparison of One-Stage and Two-Stage Assay Methods - Nilsson, I M; Kirkwood, T B L; Barrowcliffe, T W (Thrombosis and Haemostasis, 1979)
The recovery and half-life of VIII: C in the plasma of severely haemophilic patients was measured by one-stage and two-stage assays after injection of two Factor VIII concentrates (Hemofil, Hyland and Fraction I-O, Kabi). Plasma volumes were measured with an Evans Blue technique, and both concentrates and post-infusion samples were measured against the same plasma standard.There was a highly significant difference in recoveries estimated by the two assay methods. The one-stage assays gave the most consistent results, in that the average recovery was 100%, whereas the two-stage assays gave only about 80% of the value expected from in vitro assays. There was no difference in recoveries between the two concentrates.The two-stage assays gave a slightly shorter half-life than the one-stage assays, and the half-life of Hemofil was also shorter than that of Fraction I-O.